2015
DOI: 10.1007/s00339-015-9254-5
|View full text |Cite
|
Sign up to set email alerts
|

Cu/TiO2 thin films prepared by reactive RF magnetron sputtering

Abstract: Cu/TiO 2 thin films were deposited on glass substrates by reactive RF magnetron sputtering technique. Crystalline structure, surface morphology and electronic structure were studied using X-ray diffraction (XRD), field emission scanning electron microscopy, atomic force microscopy and X-ray photoelectron spectroscopy (XPS). Transmittance and absorptance of these films were characterized by UV-Vis spectroscopy. XRD patterns demonstrate that TiO 2 films deposited on glass substrate at 300°C are observed to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…Accordingly, Cu2p 3/2,1/2 core level peaks around 933.5 and 953.4 eV with corresponding satellite peaks and spin-orbit separation of 19.9 eV are assigned to Cu 2+ in these type of materials. 18,25,26 Satellite peaks are characteristics of oxidized transition metals especially, Fe, Co, Ni and Cu. 27 It has been well documented that an additional excitation of a second electron occurs during emission of a photoelectron of a core level creating a hole in it.…”
Section: Xps Studiesmentioning
confidence: 99%
“…Accordingly, Cu2p 3/2,1/2 core level peaks around 933.5 and 953.4 eV with corresponding satellite peaks and spin-orbit separation of 19.9 eV are assigned to Cu 2+ in these type of materials. 18,25,26 Satellite peaks are characteristics of oxidized transition metals especially, Fe, Co, Ni and Cu. 27 It has been well documented that an additional excitation of a second electron occurs during emission of a photoelectron of a core level creating a hole in it.…”
Section: Xps Studiesmentioning
confidence: 99%
“…5(e), it could be seen that the binding energy values were 464.22 eV and 458.48 eV, belonging to Ti 2p 1/2 and Ti 2p 3/2 , respectively, indicating the appearance of Ti 4+ . 40,41 As shown in Fig. 5(f), the co-doping of N, Fe and Zn did not change the valence state of Ti, which was still in the valence state of Ti 4+ .…”
Section: Resultsmentioning
confidence: 82%
“… In Mo/TiO 2 films, the titanium is present in +4 oxidation state as in pure TiO 2 , and the addition of Mo does not influence the nature of the Ti 4+ species significantly. The O1s core level spectra of all films, shown in Figure D, contain a main peak at ~530.0 eV, which is attributed to oxide materials only . The relative surface concentrations of Mo and Ti in the thin films are calculated from the integrated peak areas and atomic sensitivity factors of Mo3d and Ti2p.…”
Section: Resultsmentioning
confidence: 95%
“…From Figure , it is observed that as‐deposited Mo/TiO 2 films with higher concentration of Mo tend to be amorphous in nature. This can be attributed to the inhibition of TiO 2 crystal growth by addition of molybdenum . Increasing the concentration of Mo also leads to a reduction in the nucleation of the crystalline phase of anatase TiO 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation